Wireless Sensor Network for Forest Fire Detection - M. Y. Hariyawan M. Y. Hariyawan; A. Gunawan A. Gunawan; E. H. Putra E. H. Putra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Forest fires are one of problems that threaten sustainability of the forest. Early prevention system for indications of forest fires is absolutely necessary. The extent of the forest to be one of the problems encountered in the forest condition monitoring. To overcome the problems of forest extent, designed a system of forest fire detection system by adopting the Wireless Sensor Network (WSN) using multiple sensor nodes. Each sensor node has a microcontroller, transmitter/receiver and three sensors. Measurement method is performed by measuring the temperature, flame, the levels of methane, hydrocarbons, and CO2 in some forest area and the combustion of peat in a simulator. From results of measurements of temperature, levels of methane, a hydrocarbon gas and CO2 in an open area indicates there are no signs of fires due to the value of the temperature, methane, hydrocarbon gas, and CO2 is below the measurement in the space simulator.